Chinese family caregivers of stroke survivors: Determinants of caregiving burden within the first six months. Issue 23 (18th May 2017) - Han, Yanhong; Liu, Yilan; Zhang, Xuelin; Tam, Wilson; Mao, Jing; Lopez, Violeta
Abstract : Aims and objectives: To describe the family caregivers' caregiving experience for stroke survivors and to identify the determinants of caregiving burden over 6 months. Background: Sociocultural factors influence the caregiving experience in China. However, little is known about the dynamic changes occurring in Chinese caregivers' burden and its determinants. Design: This is a prospective longitudinal study. Methods: A total of 328 participants (164 stroke survivors and 164 family caregivers) from the neurological units of three hospitals in Shiyan were examined during a 6‐month period at 1–2 days before discharge (T1) and 3 weeks (T2), 3 months (T3) and 6 months (T4) postdischarge using the Short Portable Mental Status Questionnaire, Multidimensional Scale of Perceived Social Support, Caregiver Strain Index and the Center for Epidemiological Studies‐Depression. Results: Of the 209 dyads recruited, 164 completed all data collection phases, with 69% of the female caregivers aged 56.04 ( SD  = 4.0; range = 22–80) years. Caregivers reported higher mean burden at T1 (7.35 ± 2.9) but slightly decreased over time at T4 (6.34 ± 3.4), had borderline mean depressive symptoms only in T1 (9.71 ± 3.2) and T2 (9.02 ± 3.8) and had moderate mean social support throughout the 6‐month period. Determinants of caregiving burden were stroke survivors' physical dependence, caregivers' age, caring hours per day, depressive symptoms and social support, which explained 46.8%–55.0% of the total variance ( p  < .05). Conclusion: Caregivers' burden remains a serious problem in the first 6 months. It is an increasing hazard, especially for those at an advanced age who have depressive symptoms and care for severely dependent stroke survivors requiring more caring hours. Relevance to clinical practice: Nurses need to be aware of and understand caregivers' cultural values and beliefs about family obligations when considering an intervention to support them in their role at home.